A Scoping Review of Audiovisual Integration Methodology: Screening for Auditory and Visual Impairment in Younger and Older Adults - Basharat, Aysha; Thayanithy, Archana; Barnett-Cowan, Michael (Frontiers in Aging Neuroscience, 2022)
With the rise of the aging population, many scientists studying multisensory integration have turned towards understanding how this process may change with age. This scoping review was conducted to understand and describe the scope and rigour with which researchers studying audiovisual sensory integration account for age-abnormal unisensory acuities. A structured search in three licensed databases revealed 2,462 articles from which 70 articles were identified for inclusion. Our search revealed that only 66% of studies measured age-abnormal hearing, 53% measured age-abnormal vision, and consistent definitions of normal or abnormal vision and hearing were not utilized among the studies that screened for sensory abilities. Further, we found that over 50% of the behavioural results stemmed from the use of 4 task categories (speech recognition/detection, response time, target discrimination tasks, and audiovisual distraction tasks), suggesting a potential bias in the multisensory integration literature to focus on response time based tasks rather than tasks that require slower responses. A total of 1056 younger adults and 4202 older participants were included in the scoping review with males composing approximately 44% and females composing 56% of the total sample and most data came from only 4 countries. Finally, only 53 out of 70 studies tested for neurological and cognitive function, and among these 53 studies there was a lack of consistent cut-offs for determining mild cognitive impairment. We recommend that studies investigating the effects of aging on multisensory integration should screen for normal vision and hearing, use the World Health Organization's (WHO) hearing loss and visual impairment cutoffs in order to maintain consistency among other aging researchers, and screen for mild cognitive impairment using the Montreal Cognitive Assessment. The secondary aim of this scoping review was to determine the feasibility of whether a meta-analysis could be conducted in the future to further quantitively evaluate the results and to assess the scope of this problem. We found that it may not be feasible to conduct a meta-analysis with the entire dataset of this scoping review. However, a meta-analysis can be conducted if stricter parameters are utilized (e.g., focusing on accuracy or response time data only).